The new insight into the role of hydroxyproline in metabolism of cancer cells - Chalecka, Magda; Hermanowicz, Justyna Magdalena; Palka, Jerzy; Surazynski, Arkadiusz (Frontiers in Cell and Developmental Biology, 2025)
Although the role of proline (Pro) in regulatory mechanisms of cell metabolism is well recognized, the interest in metabolic significance of hydroxyproline (Hyp) has received little attention. Hyp was considered as a waste metabolite of protein degradation, mainly degradation of collagen. This amino acid is not synthesized de novo and is not incorporated into proteins. Hyp is a product of Pro hydroxylation in proteins by specific Pro hydroxylase. Therefore, Hyp is derived from degradation of proteins, and it is further metabolized by specific Hyp dehydrogenase 2 (PRODH2), known also as a Hyp oxidase (OH-POX). The enzyme catalyzes conversion of Hyp into Δ1-pyrroline-3-OH-5-carboxylic acid (OH-P5C), yielding electrons that are used in electron transport chain for ATP production. However, in certain conditions the electrons are accepted by oxygen forming reactive oxygen species (ROS). The product, OH-P5C could be also converted by OH-P5C reductase to recycle NADP+ in pentose phosphate pathway (PPP), yielding nucleotides for DNA synthesis. Interestingly, Pro hydroxylase requires the same cofactors (α-KG, ascorbate and Fe2+) as a DNA and histone demethylases, suggesting the role of Pro hydroxylation in epigenetic regulation. Hyp could be also converted to highly energetic amino acid, glycine (Gly). Of great importance is the role of Hyp in upregulation of transcriptional activity of hypoxia-inducible factor 1α (HIF-1α), inducing angiogenesis and metastasis. Therefore, Hyp is involved in several critical metabolic processes regulating DNA synthesis, gene expression, apoptosis/survival, angiogenesis, metastasis and energy production, suggesting a key role of Hyp in reprogramming metabolism of cancer cells. It suggests that Hyp metabolism could be considered as a target in novel experimental strategy for cancer treatment.